Impact of iron ore mining activities on the rhizosphere fungal communities of Musa basjoo, Apegdalus persica, and Triticum aestivum L. - Wan, Caijing; Wang, Xinhui; Luo, Yuan; Chen, Sumin; Chen, Shuyi; Yu, Xin; Wang, Ying; Liu, Bingliang; Li, Qiang (Frontiers in Microbiology, 2025)
Iron ore mining has damaged the natural environment and affected the ecological balance of the surrounding areas. The purpose of this study was to investigate the effects of iron ore mining on fungal communities in the rhizosphere soils of plantain, peach, and wheat. The results revealed that, due to iron ore mining, the pH value of the soil in the mining area generally exhibited weak acidity, and the Fe and TP contents increased significantly (P < 0.05). Notably, iron ore mining reduced fungal diversity in the rhizosphere, and only the wheat group presented a significant reduction in fungal diversity (P < 0.05). Moreover, the relative abundances of Cladosporiaceae, Cladosporium, and Sarocladium in the soil samples decreased due to iron ore mining. Conversely, the relative abundances of Fusarium and Mortierella in the soil samples were markedly enhanced by mining activities (P < 0.05). Beta diversity analysis revealed significant differences between the rhizosphere soil fungal communities of the three plants growing in the iron ore area and those growing in the non-iron ore area. The degree of variation among the different plants also varied. The Animal Pathogen-Endophyte-Fungal Parasite-Plant Pathogen-Wood Saprotroph guild was the dominant guild in the rhizosphere soil of the plants in the mining area. In summary, the results of this study help elucidate the effects of iron ore mining on fungal communities in the rhizosphere soil and provide a theoretical basis for screening fungi that can restore the ecology of the iron ore mining area.